Students’ Perception of Online Learning during COVID-19 Pandemic: A Case Study on the English Students of STKIP Pamane Talino - Antonius Setyawan Nur Agung; Monika Widyastuti Surtikanti; Charito A. Quinones, OP (Politeknik Negeri Bali, 2020)
The pandemic of COVID-19 has forced the Indonesian government through its Ministry of Education and Culture to implement policies moving conventional classroom to online classroom. The current study is a collective case study consisting of analysis of survey on students’ perceptions of their online learning during the pandemic. Sixty-six students of English Language Education Study Program at Pamane Talino College of Education (STKIP Pamane Talino) were involved. Their perceptions of their online classroom that were recorded through a survey. The recorded perceptions are in terms of students’ participation, accessibility, material and assignment delivery, and the use of e-learning platforms. The results were then summarized into tables and narrative descriptions. The study identified three major obstacles in conducting online learning in English Language Education Study Program at STKIP Pamane Talino: the first is availability and sustainability of internet connection, the second is accessibility of the teaching media, and the last is the compatibility of tools to access the media. The result of the current study suggests that accessibility is still the major factor influencing the success of online learning. Online learning for English Language Education Study Program at STKIP Pamane Talino, and potentially Indonesia in general, requires some more friendly platforms so that students’ participation can be increased. This is especially for students who reside in rural areas with limited internet connections and other support systems